تخطيط وجدولة تنفيذ مشاريع الخدمات البلدية بأستخدام نظام المعلومات الجغرافية(GIS ) بحث تطبيقي في مدينة الهندية ـ محافظة كربلاء المقدسة - عبد الوهاب نادية لطفي; عبد المجيد نوار رعد (Journal of Economics and Administrative Sciences, 2015)
The research has handled an important service sector in Iraq which is the municipals sector since it is connected directly and closely with the services presented to the citizens, and because the process of accomplishing the projects needs planning and scheduling for implementing these projects according to the available financial allocating and it was no choice but finding modern methods that help succeeding the processes of planning through making use of Geographic Information system (GIS) in providing the necessary information in scheduling the projects since it is considered as one of the tools that conveys the occurred in collecting the huge amount of the locative data related to the items of the essential design of the towns . The problem of the research was represented by the large shortage in the presentation of the municipal services especially (paving، cladding، and Flooring ) in addition to the retrogression of these services in the total essential design of the town of Hindia with the weakness of the established plans which demonstrates the course of the municipals and its future plans، which we can evaluate the performance of these municipals about the projects that are going to be accomplished during the coming periods with the concentration of providing the services to certain areas while neglecting the other areas. The research aims to prepare schedules and charts to the areas belong to the Hindia Town by using the Satellite pictures and treating and producing them with the possibility of diagnosis the level of services presented in each area that belongs to the town under consideration, which would help in making the right decision related to the execution of the projects in such a way that secures the prevention of interference with projects of other enterprises in the town. The research reached many conclusions such as the absence of general plan that can guide the municipal establishments in the Hindia Town because of the unavailability of the data related to the level of the services presented and the actual need for different areas in the town of these services. One of the recommendations of the research is the necessity of the good future planning for executing the public services projects in the town with the establishment of central an integrated information Bank for the geographical information and the updating it continually to be used by the municipal establishments and the other authorities related to the process of planning to the future projects.